2002
DOI: 10.1081/cbi-120004222
|View full text |Cite
|
Sign up to set email alerts
|

Circadian period lengths of lipid synthesis mutants (cel,chol-1) ofNeurosporashow defective temperature, but intact pH-compensation

Abstract: The influence of extracellular pH on the circadian sporulation rhythm of Neurospora crassa has been investigated for the mutants chol-1 and cel. Both mutants have a defect in the lipid synthesis pathway and require either choline or palmitate, respectively, as supplements for normal growth. The chol-1 and cel mutants also show an impaired temperature-compensation when growing on minimal medium. We investigated the possible correlation between loss of temperature-and pH-compensation in cel and chol-1 similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…We confirmed that strain PL32-54 (bd;chol-1;csp-1) displays a characteristic elongated rhythm (period length Ϸ 60 h) on race tubes without choline supplementation and a normal conidiation rhythm (period length Ϸ 22 h) on race tubes supplemented with 100 M choline (Fig. 1A), consistent with previous results (30,32). To measure molecular rhythms in liquid cultures, bd;chol-1;csp-1 was cultured with or without choline supplementation for 12-56 h in light followed, respectively, by 48 to 4 h in darkness, so by harvest all cultures had been growing with or without choline supplementation for at least 60 h (34).…”
Section: Frq Oscillation In Choline Depletionsupporting
confidence: 81%
See 1 more Smart Citation
“…We confirmed that strain PL32-54 (bd;chol-1;csp-1) displays a characteristic elongated rhythm (period length Ϸ 60 h) on race tubes without choline supplementation and a normal conidiation rhythm (period length Ϸ 22 h) on race tubes supplemented with 100 M choline (Fig. 1A), consistent with previous results (30,32). To measure molecular rhythms in liquid cultures, bd;chol-1;csp-1 was cultured with or without choline supplementation for 12-56 h in light followed, respectively, by 48 to 4 h in darkness, so by harvest all cultures had been growing with or without choline supplementation for at least 60 h (34).…”
Section: Frq Oscillation In Choline Depletionsupporting
confidence: 81%
“…The mutant shows a conidiation rhythm, controlled by a choline deficiency oscillator (CDO), with a period Ͼ50 h under choline starvation (30) that can be entrained by light to periods near its intrinsic length but not to periods within the circadian range. The rhythm is pH-compensated but not temperature-compensated (30)(31)(32). The period length of the rhythm reflects the degree of choline starvation, but the allelic states of the frq or wc genes have little or no effect on the rhythm.…”
mentioning
confidence: 99%
“…Fatty acid synthesis mutants of Neurospora crassa have a long‐period circadian phenotype and/or defective temperature compensation (Lakin‐Thomas & Brody, 2000; Ruoff & Slewa, 2002). In Arabidopsis , mutation of FAD2 means that the free‐running period of leaf movement does not shorten as it does in wild‐type plants when grown at 27°C (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The conidiation phenotypes of the multiplemutant strains were assayed in free-running conditions (DD, 22 °C) on medium without choline. Choline-free medium reduces the growth rate of chol-1 strains and allows expression of long-period rhythmicity in both frq + and frq null strains (Lakin-Thomas, 1996, 1998Lakin-Thomas and Brody, 2000;Ruoff and Slewa, 2002;Shi et al, 2007). In Figure 1, the "wildtype" strain (carrying the ras-1 bd and csp-1 mutations but wild type for chol-1, frq, and prd) displays the expected conidiation rhythmicity.…”
Section: Effects Of Prd Mutations On Free-running Rhythms In Chol-1mentioning
confidence: 99%